2020
DOI: 10.1080/15685551.2020.1812832
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, conjugating capacity and biocompatibility evaluation of a novel amphiphilic polynorbornene

Abstract: Polynorbornenes, prepared by the 'living' and 'controlled' ring-opening metathesis polymerization (ROMP) method, have emerged as a stimuli-sensitive new class of polymer carriers. Herein, we reported a novel amphiphilic diblock polynorbornene, PNCHO-b-PNTEG, containing active benzaldehyde units, which exhibited good conjugating capacity to amino-containing molecules (e.g., doxorubicin (DOX)) via the pH-sensitive Schiff base linkage. The copolymer and its conjugate with DOX, DOX-PNCHO-b-PNTEG, were adequately a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…An additional concern with this system pertains to the toxicity and in vivo persistence of the polynorbornene backbone produced by ROMP disassembly. Several studies have demonstrated that polynorbornenes are not cytotoxic. However, because these macromolecules feature an all-carbon backbone, they are not readily degradable. Nevertheless, recent work has shown that doping the pool of norbornene ROMP precursors with silyl ether-based cyclic olefins results in degradable backbones with significantly improved long-term clearance profiles .…”
Section: Discussionmentioning
confidence: 99%
“…An additional concern with this system pertains to the toxicity and in vivo persistence of the polynorbornene backbone produced by ROMP disassembly. Several studies have demonstrated that polynorbornenes are not cytotoxic. However, because these macromolecules feature an all-carbon backbone, they are not readily degradable. Nevertheless, recent work has shown that doping the pool of norbornene ROMP precursors with silyl ether-based cyclic olefins results in degradable backbones with significantly improved long-term clearance profiles .…”
Section: Discussionmentioning
confidence: 99%
“…DDS based on polymer micelles composed of (oxa) norbornene derivatives with OEG-modified segments as the hydrophilic shells and drug-bearing segments as the hydrophobic core have been extensively investigated, and a wide variety of drug molecules have been introduced. Examples of such drugs include birabresib, 293 bortezomib, 295,305 camptothecin, 285,288 cisplatin, 288,[306][307][308] coumarin, [309][310][311][312] DACHplatin, 250 dexamethasone, 295 doxorubicin, 261,[285][286][287][288]296,[313][314][315][316][317][318] folate, 253,254,256 isoniazid, 319,320 paclitaxel, 217,258,290,292,310,[321][322][323] piplatine, 258 pomalidomide, 295 rifampicin, 319 retinol, 320,324 and vorinostat, 246 which have all demonstrated efficacy comparable to that of the introduced agent.…”
Section: Drugs For Drug Delivery System (Dds)mentioning
confidence: 99%